1994
DOI: 10.1590/s0101-81751994000400009
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and growth curves of Macrobrachium Carcinus (Linnaeus) (Crustacea, Decapoda, Palaemonidae) from Ribeira de Iguape River, southern Brazil

Abstract: ABSTRACT. ln this paper. femalo Macmhrachilllll corei""". (Linnaeus. 1758) maturation curve. wcight / knglh rdationship. kllgth ano wl.!ight growth curvl!s wcrc stuoieo . Prawns wer.: eaplUreo. hy traps . in Riheira de I~uape river (24°S and 4rW). southan Brazil. There were used 207 females. It was observed that M. cllrcinlls presents several spawnings during its !ife ,ycle and reprodu,tive paiod goes on. ai leasttill six years old. Weighlllength rdalionship can be represented for the equalion W=8.73 E-3 L3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…While Gabche & Hockey (1995) Isaac (1990) had demonstrated that growth parameters estimated from ELEFAN I could be biased as a result of individual growth variability, seasonal oscillations in growth, the restructuring procedure, sizedependent selection, variable recruitment period and large size-class interval. Using the growth performance index or phi prime (Φ') which is the basis of comparison of growth parameters (Moreau et al, 1986;Munro & Pauly, 1983;Pauly, 1991) and which also takes into consideration L ∞ and K, the results in this study fall within an acceptable range since the Φ' values obtained in this study (2.75 and 2.67 for males and females) are comparable with those for M. carcinus (2.34) (Valenti et al 1994), M. vollenhovenii (2.93) (Gabche & Hockey 1995), and 2.47 (Etim & Sankare, 1998). In contrast, the estimated longevity of the species varied widely from 11 months (Gabche & Hockey, 1995) to 39.6 months (Etim & Sankare, 1998).…”
Section: Resultssupporting
confidence: 70%
“…While Gabche & Hockey (1995) Isaac (1990) had demonstrated that growth parameters estimated from ELEFAN I could be biased as a result of individual growth variability, seasonal oscillations in growth, the restructuring procedure, sizedependent selection, variable recruitment period and large size-class interval. Using the growth performance index or phi prime (Φ') which is the basis of comparison of growth parameters (Moreau et al, 1986;Munro & Pauly, 1983;Pauly, 1991) and which also takes into consideration L ∞ and K, the results in this study fall within an acceptable range since the Φ' values obtained in this study (2.75 and 2.67 for males and females) are comparable with those for M. carcinus (2.34) (Valenti et al 1994), M. vollenhovenii (2.93) (Gabche & Hockey 1995), and 2.47 (Etim & Sankare, 1998). In contrast, the estimated longevity of the species varied widely from 11 months (Gabche & Hockey, 1995) to 39.6 months (Etim & Sankare, 1998).…”
Section: Resultssupporting
confidence: 70%
“…Von Bertalanffy's growth curve (VON BERTALANFFY 1938), although commonly used for fishes (SANTOS 1978) and for a variety of crustaceans, especially decapods (FONTOURA 1989, VALENTI et al 1994, BARROS & FONTOURA 1996, BUENO et al 2000, NORO & BUCKUP 2003 has rarely been used for terrestrial isopods. MCQUEEN & CARNIO (1974) studied the growth of Porcellio spinicornis Say, 1818 using von Bertalanffy's model, reformulated to consider growth measured in terms of weight.…”
Section: Philoscia Muscorummentioning
confidence: 99%
“…Sexual dimorphism has been widely documented for epigeal crayfish and prawns (Weagle and Ozburn 1970;Lobao et al 1986;Valenti et al 1987Valenti et al , 1994Hernández-Guzmán et al 1999), notably in the proportions of the chelae. In the epigeal environment the main selective force that induces sexual differentiation in chelae is reproductive behaviour, since in general males show aggressive and dominant behaviour to conspecifics (Bovbjerg 1970; Progressive troglomorphism in cave decapods 259 Rabeni 1985;Sö derbäck 1991).…”
Section: Discussionmentioning
confidence: 99%